Spiritual Health Survey and Obtaining Spiritual History in the Paradigm of Islam and Christianity - Minoo Asadzandi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research explores the Islamic paradigm of spiritual health assessment, particularly its divergence from Christian traditions in measuring religiosity. While spiritual health is often equated with religious well-being, especially among Muslim scholars, assessing religiosity may violate on privacy, induce insecurity, and contradict Islamic jurisprudential principles. This research aims to clarify whether Islamic doctrine permits the evaluation of religiosity and the collection of spiritual histories through confession or inquiry. Employing a mixed-methods approach based on Creswell’s sequential explanatory model and the Sound Heart Theory, this research integrates qualitative content analysis with quantitative data from clinical implementation. Validity is ensured through triangulation and expert review in spiritual health scholarship. The findings indicate that Islam prohibits the investigation of hidden beliefs, confessions of sin, and intrusive questioning, as such practices violate human dignity and privacy. In contrast to Catholic traditions, Islamic jurisprudence prioritizes the protection of spiritual secrecy and discourages external measurements of faith. The research concludes that spiritual health providers should adopt culturally grounded, non-invasive strategies, avoiding religiosity metrics and instead promoting family-centered spiritual self-care education. These findings advocate for paradigm-sensitive approaches in spiritual care across diverse religious contexts and underscore the necessity of aligning assessment models with theological principles and sociocultural norms.